Industrial practitioner's perception on the application of exoskeleton system in automotive assembly industries: A Malaysian case study - Woun Yoong Gan; Raja Ariffin Raja Ghazilla; Hwa Jen Yap; Suman Selvarajoo (Heliyon, 2024)
The automotive industry is a key manufacturing industry for the Malaysian economy, where manual jobs and task are still common. Hence, Work-related Musculoskeletal Disorders (WMSD) is a common type of injury among workers. Exoskeleton system has gained global traction as a possible solution to reduce the risk of MSD among workers. Nonetheless, the application of exoskeleton in the automotive industry in Malaysia remains unknown. As such, this study attempts to provide insight into the industry's perception on the potential of exoskeleton application within the context of Malaysian automotive assembly sector. Therefore, a total of 52 management level respondents from various manufacturers participated in this study. It is found that, although the technology seems to be relatively new and disruptive, the respondents have a positive perception towards it with an acceptance rate of 86.5%. Cost of implementation exoskeleton technologies seems to be primary concern from the respondents, other concern such as maintenance cost and ease of application into existing application is also highlighted.